Application of a vertical centrifugation technique to develop a de-oiling machine for crispy fried enoki mushrooms - Sumrit, Thawanrat; Swaeng-ngam, Surintraporn; Inrirai, Patcharaporn; Suriwong, Voraluck; Jantarasricha, Tanakorn (Asia-Pacific Journal of Science and Technology, 2025)
The aim of this research was to develop a de-oiling machine and evaluate its efficiency when making crispy fried enoki mushrooms in terms of reducing residual oil in the product after the frying process. This machine had five essential components: vertical centrifugation, an external tank, a motor unit, oil drainage, and a speed adjustment mechanism. After the frying process, the crispy enoki mushrooms had an average weight of 150 g. The adjustment of the de-oiling speed levels was examined using three different speeds: 6, 7, and 8, while the de-oiling durations were set at 30, 40, and 50 sec. The results revealed that the use of different operating conditions affected the removal of oil. The de-oiling process, conducted at speed level 8 for a duration of 30 sec, resulted in a weight loss of 8.41±0.72% after the oil removal. The aw value obtained was 0.32±0.00, while the hardness value was 30.60±1.46 N. Additionally, the fat content was determined to be 31.32± 1.08%. This operation enabled improved textural qualities compared to other conditions. Compared to the control sample, the samples with lower fat content exhibited increased crispiness. Meanwhile, the control sample had a fat content of 45.05±0.28% and a hardness of 28.36±0.21 N. The efficiency of oil removal from crispy fried enoki mushrooms was enhanced using this developed de-oiling machinery, which ensures that the texture and flavor of these mushrooms are preserved after the frying process.